Rancang Bangun Monitoring Ruang CCTV Server Menggunakan Raspberry Pi Di Sekolah Pelita Harapan Lippo Village - Muhamad Irsan; Edy Bill Stephen; Agus Supriyono (Teknik Informatika, 2019)
Computer devices are a unit that is useful both now and in the future, not the device, but the data stored in it is very valuable both master data, transactions and reports. One of the factors that causes damaged computer components is the room temperature that exceeds the provisions, namely 21-230 celsius. The sensors used are 3 DS18B20 temperature sensors and MQ2 smoke sensor. Both types of sensors are placed inside the server room, besides that, a buzzer is also added to produce sound if the temperature is more than 250 Celsius. The whole program is connected to Raspberry Pi and uses the python program language. It is expected that with the presence of temperature and smoke sensors, the server room will be monitored so that problems regarding damaged devices can be avoided.